Deficiency of Glycosyl-Phosphatidylinositol-Linked Membrane Glycoproteins of Leukocytes in Paroxysmal Nocturnal Hemoglobinuria, Description of a New Diagnostic Cytofluorometric Assay - Schoot, C.Ellen van der; Huizinga, Tom W.J.; Veer-Korthof, Elisabeth T. van 't; Wijmans, Rosemarie; Pinkster, Jantina; Borne, Albert E.G.Kr. von dem (Blood, 1990)
Paroxysmal nocturnal hemoglobinuria (PNH) is a disease that affects not only red cells, but other blood cells as well. The common defect is supposed to be an acquired deficiency of glycosyl-phosphatidylinositol (GPI)-anchored membrane proteins, which may be present already at the hematopoietic stem cell level. Recently, a panel of monoclonal antibodies (MoAbs) has become available directed against various GPI-linked membrane proteins. This makes it possible to study various cell lineages for the deficiency of such proteins in PNH in more detail. Using cytofluorogra-phy, we could show that the granulocytes of 20 different PNH patients miss not only GPI-linked FcRIII (CD16 antigen), but also three other GPI-linked proteins, ie, CD24 antigen, CD67 antigen and a granulocyte-specific 50 to 80 Kd antigen. The affected granulocytes were not only neutrophils but also eosinophils, as was found in a more detailed analysis of three patients. Moreover, in all 10 PNH patients tested, the monocytes were found to be deficient for the GPI-linked CD14 antigen, and we found with CD24 and CD55 (DAF) antibodies that lymphocytes may be involved as well. However, abnormal B and T lymphocytes were detected only in a subset of patients (2 of 10 tested). The uniform deficiency of GPI-linked proteins of granulocytes allows the introduction of a new diagnostic cytofluorometric assay for PNH with MoAbs against GPI-linked granulocytic antigens. This test was positive in all PNH patients studied and not in a group of 40 control patients or 50 normal donors, with the exception of three of 16 aplastic anemia (AA) patients. In the three AA patients. subpopulations (10% to 20%) of PNH granulocytes could be detected, whereas these patients had a negative acidified serum (Ham) test. This indicates that the new test is more sensitive than the Ham test and allows the early diagnosis of PNH in AA. An advantage of the neutrophil assay is that, in contrast to the Ham test, it is not influenced by recent red-cell transfusions. Moreover, it is possible to quantify the number of affected cells by single cell analysis.